Pengaruh Bahan Isolasi Termal Terhadap Perpindahan Kalor Pada Tangki Penyimpanan Steam Untuk Meminimalisir Heat Loss dan Tekanan - Nurlianna Tarigan (JURNAL VOKASI TEKNIK, 2023)
Back Pressure Vessel (BPV) is a tank that serves as a reservoir for steam generated by the turbine output. Pressure vessels are used as reservoirs for fluids, both liquid and gas. BPV not only plays a role in storing and distributing steam, but also works as a controller of incoming and outgoing steam. Pressure at BPV 3.5 bar and temperature 138℃. This pressurized tank is one of the important industrial processing tools, especially for the palm oil processing industry. In the process prior to steam delivery, one of the most important components is the steam storage medium, because its function is to keep the steam obtained from the turbine output from being lost, so that it can be distributed. Therefore, a steam storage tank is needed that can withstand heat loss so that the temperature and pressure do not drop. Therefore, an insulating material (thermal insulation) is used which has poor properties in conducting heat to the tank wall in order to hold the heat out of the tank into the environment quickly.Glass woll thermal insulationn material is better than rock woll thermal insulation material with the same thickness of thermalinsulation material of 50 mm, the heat loss for rock wool is 16.361,3726 kcal/hour and glass wool is 16.244,8158  kcal/hour with a comparison of glass wool that can withstand heat. Better at 116,5568 kcal/hour.